Suppression of the ssb-1 and ssb-113 mutations of Escherichia coli by a wild-type rep gene, NaCl, and glucose. - Tessman, E S (1982)
The ssb-1 mutation confers severe temperature sensitivity and UV sensitivity on many strains of Escherichia coli K-12 and C, including strain C1412. However, ssb-1 confers only slight temperature sensitivity and slight UV sensitivity on strain C1a, suggesting that strain C1a contains extragenic suppressors of ssb-1. We found that introduction of the wild-type rep gene from C1a into strain C1412 ssb-1 gave strong suppression of temperature sensitivity and moderate suppression of UV sensitivity. Also, the C1a rep+ gene mildly suppressed the temperature sensitivity conferred by the ssb-113 mutation, formerly called lexC113. Suppression of the C1412 ssb-1 growth defect by C1a rep+ rendered the cells Gro- for phi X174. In contrast to the positive suppression of ssb-1 and ssb-113 by a wild-type rep gene, mutant rep alleles enhanced the severity of the ssb-1 defect, with several C1a ssb-1 double mutants being either more temperature sensitive or more UV sensitive than C1a ssb-1, depending on which mutant rep allele was used. As a control, the same rep alleles in combination with a dnaB mutation gave an allele-independent increase in temperature sensitivity. Our results on suppression of ssb-1 by rep and on the role of the genetic background in this suppression suggested that the rep and ssb proteins interact to form a subcomplex of the total DNA replication complex and that this subcomplex has some function in repair. The effects of NaCl and glucose on suppression of both the temperature sensitivity and the UV sensitivity conferred by ssb-1 and ssb-113 are described. The degree of suppression of temperature sensitivity by salt or glucose was dependent on the source of the wild-type rep allele, as well as on the genetic background.